Efektivitas Layanan Informasi Cara Memahami Diri dan Lingkungan dalam Pemilihan Karir Siswa - Durrotunnisa Durrotunnisa; Nursaida R (Universitas Tadulako, 2021)
This research aims to explain the effectiveness of information services on understanding ourselves and the environment on career choices of grade XI students of SMA Negeri 1 Sarudu. The research subjects were 30 students. The main research instrument was a questionnaire. The collected data obtained were analyzed descriptively and inferentially. The results of the descriptive analysis showed that the student's career choice before attending the information service on understanding ourselves and the environment is 43,3% of students have the right career choice, 33.3% of students have moderately accurate career choices, and 23,3% of students have inappropriate career choices. After attending information services on understanding ourselves and the environment, students' career choice improves that 20% of students have definite career choices, 46,6% of students have accurate career choices, and 33,3% of students have moderately accurate career choices. Based on the results, it can be concluded that information services on understanding ourselves and the environment are effective in the career choices of grade XI students of SMA Negeri 1 Sarudu.